Modeling of suspended sediment concentrations under combined wave-current flow over rippled bed. (5th December 2017) - Lu, Jing; Wang, Xiao Hua; Babanin, Alexander V.; Aijaz, Saima; Sun, Younjong; Teng, Yong; Jung, Kyung-Tae; Qiao, Fangli
Abstract: Ripples appear and disappear dynamically on coastal bed. The bottom stress can significantly be enhanced when ripples appear, and then the sediment transport will be influenced by the ripple-enhanced stress. However, ripples' impact on suspended sediments is seldom discussed. In this study, a bedform (ripples) module based on combined wave and current flow is coupled with a bottom boundary layer (BBL) model. This BBL model outputs our improved bottom shear stress (BSS) to both the sediment model (UNSW-sed) and the hydrodynamic model (POM). Model results in Jervis Bay of Australia show that the simulated suspended sediment concentration (SSC) of an abrupt rising is significantly improved by considering ripples rather than setting a uniform roughness ( K b ) without ripples. However, the SSC is still underestimated by using previous schemes. Differently from the previous estimation of ripple-enhanced shear velocity U ∗ c w e, noted as U ∗ c w e _ N L, we introduce an U ∗ c w e improved by calculating through ripple-enhanced ripple-enhanced K b, which is noted as U ∗ c w e _ K b . Simulation shows that U ∗ c w e _ K b produces significantly increased SSC under high wave conditions, resulting in reasonable agreements with the measurements. The wave friction factor f w is shown to play a crucial role in causing the difference between U ∗ c w e _ K b and U ∗ c w e _ N L .